PSYCHOLOGICAL STUDY OF THE MAIN CHARACTERS IN THE NOVEL PRIMADONA BY ACHMAD MUNIF - Dwi Mutia Chan (Kantor Bahasa Kepulauan Riau, 2022)
This study aims to describe the psychology of the main character in the novel Primadona by Achmad Munif. The research problem is focused on the form of behavior displayed by the main character, the motives of the main behavior, and the relationship with the main character's personality. This research is a descriptive qualitative research. The research was conducted by analyzing the content of the novel seen from the behavior displayed by the main character. Data collection was done by observing the behavior of the main character and the motives behind it and associated with psychological aspects. This research prioritizes the study of the psychology of the main character from the behavior of the character and the motives behind it. The results of this study indicate that the behavior displayed by the main character is caused by several motives, namely; (1) being aware of the family situation, (2) not wanting to be selfish, (3) maintaining honor and chastity, (4) changing life for the better. The motives of the main character's behavior are based on psychological aspects such as ego and superego. These two aspects of psychology are the most basic factors and greatly affect the behavior or psychological activities of the main